Divergent patterns in institutional entrepreneurship of MNCs in emerging economies. Issue 3 (3rd July 2017) - Becker-Ritterspach, Florian; Lange, Knut; Becker-Ritterspach, Jutta
Abstract : Purpose: The purpose of this paper is to develop a theoretical framework that addresses the question of how and why multinational corporations (MNCs) from developed economies engage in divergent patterns of institutional entrepreneurship (IE) in emerging markets. Design/methodology/approach: The authors combine IB's concept of institutional voids with comparative capitalism's insights into the institutional embeddedness of firm capabilities and IE. This theoretical cross-fertilisation is instrumental in developing a refined understanding of institutional voids and how MNCs proactively engage with them. Findings: The authors emphasise the notion of institutional voids as a relative concept and, thereby, move away from an ethnocentric view of emerging markets as "empty spaces" that are void of institutions. The authors' framework proposes that MNCs from liberal and coordinated market economies experience institutional voids differently and engage in different patterns of IE. Research limitations/implications: The main limitation of this work is that the propositions are restricted to the country-of-origin effect and that the observations are based on anecdotal evidence only. Against these limitations the authors call for a more comprehensive research agenda in their conclusion. Social implications: The paper sensitises policymakers in emerging markets for the potentially different patterns of involvement of MNCs in their institutional environments. Specifically, the authors argue that MNCs may have a strong inclination to rebuild critical elements of their home country's institutional setting in emerging markets. This touches upon questions of national sovereignty and highlights the need for emerging market policymakers to decide which kinds of institutional settings they would like or not like to see imported. Originality/value: The paper provides a new and critical perspective of the mainstream IB concept of institutional voids. The authors' key contribution is to highlight that the home country institutional context may substantially matter in how MNCs perceive and respond to institutional voids in emerging markets.